Cultura organizacional e diferença geracional : desafios e expectativas nas organizações - Vieira, Marcelo Cristian (2014)
Studies on generations in Brazil, are presented as an emerging theme, and issues related to the entry of new active workforce, the greater permanence of employees in enterprises after retirement and social relations produced by generations in the organizational context, are points that support the importance of the issue and generate interest in understanding them. Organizations, routinely, are having to learn to deal with frameworks increasingly different employees, where the world view and way of dealing with the situations are related to the generation (Baby Boomers, GenX and GenY) in which each does party. This study sought to analyze and interpret social working relationships between different generations in an organization of higher education in northwest Paraná. Therefore, a field study of a qualitative nature, where the methodological approach was case study was developed. Primary data were collected through interview techniques with semi-structured and a focus group. Regarding the secondary data, they were collected from documents assigned by the institution. Thus, we sought through descriptive and interpretative analysis, understand and describe the characteristics of a given population phenomenon and to then understand how to establish social relationships work between different generations within the organization.